Meta analysis study: Effectiveness of problem based learning on Indonesian students' mathematical reasoning ability - Fitriyah, Ihda Mutimmatul; Putro, Nur Hidayanto Pancoro Setyo; Apino, Ezi (Jurnal Riset Pendidikan Matematika, 2022)
Problem-Based Learning has been studied over three decades in various subjects and schools, This meta-analysis study aimed to synthesize the most recent findings of the effect of Problem-Based Learning (PBL), specifically on students' mathematical reasoning ability. The data were obtained from relevant primary studies published in national and international journals or proceedings during 2014-2021. Ten effect sizes from eight studies that fulfilled the inclusion criteria were analyzed using a systematic review and meta-analysis. JASP 0.15.0.0 software was used to measure the formula of Hedges g to determine the effect size. The result showed that PBL has a strong effect on students' mathematical reasoning ability (gRE = 2.062, 95% CI [1.436, 2.689], p < 0.001) when compared to traditional learning. The results of the analysis of moderator variables revealed that publication year (Qb = 5.460, p < 0.05) and sampling technique (Qb = 9.032, p < 0.05) had significant effect on the effectiveness of PBL on students' mathematical reasoning ability, while educational levels (Qb = 1.649, p > 0.05), sample size (Qb = 2.081, p > 0.05) and publication sources (Qb = 0.573, p > 0.05) did not show any significant effect. The result of this study provides important information for further meta-analysis study and the implementation of PBL in mathematics learning.